The Influence of Ethical Ideology on Ethical Judgment with Professional Commitment as Mediator (Study on Public Accountant Firm Auditors in Malang) - Livi Meiga Puteri; Nurika Restuningdiah; Makaryanawati Makaryanawati (Journal of Applied Business, Taxation and Economics Research, 2023)
This study aims to determine the effect of ethical ideology on ethical judgment with professional commitment as a mediator. The respondents of this study were KAP auditors in Malang City. The distribution of questionnaires used in the study obtained a sample of 77 respondents. This research was tested using path analysis, the results of the study concluded that ethical ideology (idealism) has a positive effect on ethical judgment and can be mediated by professional commitment, while ethical ideology (relativism) hurts ethical judgment and can be mediated by professional commitment. This study shows that the higher the moral idealism of an auditor, the higher the auditor's desire to comply with the rules and principles of accounting ethics compared to auditors who have moral relativism. Relativistic auditors tend to be unprofessional and more lenient when making ethical decisions